Immunogenicity and efficacy of a feed-based bivalent vaccine against streptococcosis and motile Aeromonad septicemia in red hybrid tilapia (Oreochromis sp.) - Mohd Ali, Nur Shidaa; Saad, Mohd Zamri; Azmai, Mohammad Noor Amal; Salleh, Annas; Mohamed Zulperi, Zarirah; Manchanayake, Tilusha; Zahaludin, Muhammad Amir Danial; Basri, Lukman; Mohamad, Aslah; Md Yasin, Ina Salwany (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Streptococcosis and motile Aeromonad septicemia (MAS) are the main bacterial diseases in tilapia culture worldwide, causing significant economic losses. Vaccination is an effective method of preventing diseases and contributes to economic sustainability. This study investigated the immuno-protective efficacy of a newly developed feed-based bivalent vaccine against streptococcosis and MAS in red hybrid tilapia. The feed-based bivalent vaccine pellet was developed by incorporating the formalin-killed S. agalactiae and A. hydrophila antigens into a commercial feed pellet with palm oil as the adjuvant. The bivalent vaccine was subjected to feed quality analyses. For immunological analyses, 900 fish (12.94 ± 0.46 g) were divided into two treatment groups in triplicate. Fish in Group 1 were unvaccinated (control), while those in Group 2 were vaccinated with the bivalent vaccine. The bivalent vaccine was delivered orally at 5 of the fishs body weight for three consecutive days on week 0, followed by boosters on weeks 2 and 6. Lysozyme and enzyme-linked immunosorbent assays (ELISAs) on serum, gut lavage, and skin mucus were performed every week for 16 weeks. Lysozyme activity in vaccinated fish was significantly (p ‰ 0.05) higher than in unvaccinated fish following vaccination. Similarly, the IgM antibody levels of vaccinated fish were significantly (p ‰ 0.05) higher after vaccination. The bivalent vaccine provided high protective efficacy against S. agalactiae (80.00 ± 10.00) and A. hydrophila (90.00 ± 10.00) and partial cross-protective efficacy against S. iniae (63.33 ± 5.77) and A. veronii (60.00 ± 10.00). During the challenge test, fewer clinical and gross lesions were observed in vaccinated fish compared with unvaccinated fish. Histopathological assessment showed less severe pathological changes in selected organs than the unvaccinated fish. This study showed that vaccination with a feed-based bivalent vaccine improves immunological responses in red hybrid tilapia, and thus protects against streptococcosis and MAS.